Expectations from 2019-20 Union Budget for Indian farm - Dastagiri, M B; Mishra, Sweta (Indian Farming, 2019)
The paper discuss the global agricultural policy of some countries, comparison and the expectation that arises from the Union Budget of 2019-20, India. Budget has always been a key towards exploring the importance that the present government provides to a particular sector. Government intervention is expected to increase the social welfare by financing the agricultural research and development, and redistributing the income by shifting the agricultural incentive. The paper analyses the trends in budget allocation, the sectors contributing higher growth rate, and the outlay, and expenditure on different schemes over the years. India is witnessing a decline in share of agriculture and allied sectors in Gross Value Added. The study observed that the growth rate between 2012-13 to 2016-17 has a fluctuating trend since 2012-13. The study also focused on comparing and analyzing different International agricultural policy models. The paper suggests focusing future policies on agriculture as a global agenda and global efforts.